PROCESS MINERALOGY FOR EVALUATING MINERALOGY, PHYSICAL AND CHEMICAL CHARACTERS OF THE TAILINGS COMES FROM GOLD PROCESSING - Tatang Wahyudi (Indonesian Mining Journal, 2014)
Based on mineralogy, physical and chemical analyses, character of gold-processing tailings from Pongkor showed relatively complex condition. Gold particles were normally included by either sulfide (pyrite, chalcopyrite, galena, arsenopyrite, sphalerite etc.) or silicate minerals (mainly quartz). The inclusion structure performed single, double or multiple forms. Single inclusion meant that gold particle(s) was encased by one mineral phase while double and multi inclusions implied that the gold was sheathed by two or more phases. Gold was distributed along the micro-cracks of either similar or different phase. Chemical analyses showed that Pongkor tailings were characterized by several elements that might be ineffective for gold leaching by cyanide. Preg-robbing solution might be occurred.